Realised edaphic niche and specialisation of the fern genus Polybotrya - Fontanie, Némo (My University, 2025)
Understanding species distribution is anchored in ecology as it sheds light on the conditions in which a species occurs. Providing well-defined species ecological niches ensures spotting indicator species and rapid environmental conditions characterisation and grants knowledge on evolutionary mechanisms and diversity patterns. This study aims to delineate the ecological niche of some species of the fern genus Polybotrya fully nested in the Neotropics. From Costa Rica to the East Atlantic Brazilian Forest, species abundance was recorded, and the edaphic condition was measured to produce their response curves along the nutrient gradient. Species responses were diverse; some appeared specific to the poor edaphic condition, while others harboured more generalist behaviour. This study raises some potential indicator species for soil conditions as well as an insight into the evolutionary history of this genus. Its results are anchored in understanding the Neotropics' diversity patterns and geological and climatic history.
Keywords: Ecology, botany, Pteridophyta, fern, ecological niche, species distribution, soil composition, HOF modelling, evolutionary history, soil map, floristic analysis, realised niche, species optima, species tolerance, Neotropics.